Sensitivity to an Illusion of Sound Location in Human Auditory Cortex - Higgins, Nathan C.; McLaughlin, Susan A.; Da Costa, Sandra; Stecker, G. Christopher (Frontiers in Systems Neuroscience, 2017)
Human listeners place greater weight on the beginning of a sound compared to the middle or end when determining sound location, creating an auditory illusion known as the Franssen effect. Here, we exploited that effect to test whether human auditory cortex (AC) represents the physical versus perceived spatial features of a sound. We used fMRI to measure AC responses to sounds that varied in perceived location due to interaural level differences (ILD) applied to sound onsets or to the full sound duration. Analysis of hemodynamic responses in AC revealed sensitivity to ILD in both full-cue (veridical) and onset-only (illusory) lateralized stimuli. Classification analysis revealed regional differences in the sensitivity to onset-only ILDs, where better classification was observed in posterior compared to primary AC. That is, restricting the ILD to sound onset–which alters the physical but not the perceptual nature of the spatial cue–did not eliminate cortical sensitivity to that cue. These results suggest that perceptual representations of auditory space emerge or are refined in higher-order AC regions, supporting the stable perception of auditory space in noisy or reverberant environments and forming the basis of illusions such as the Franssen effect.